2020
DOI: 10.1088/1742-6596/1660/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of liquid residues of Cymbopogon citratus oil extracts

Abstract: Cymbopogon citratus (Lemongrass) is a type of medicinal herb that widely used in Asia. This study aims to investigate the antimicrobial activity of liquid residues of ethanolic and aqueous Cymbopogon citratus oil extracts. Residues of ethanolic and aqueous Cymbopogon citratus oil extracts were used to study their antimicrobial activities for Staphylococcus aureus; Staphylococcus epidermidis; Pseudomonas aeruginosa and Candida albicans which were isolated from burned skin of patients suffering from burns at Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…There are few studies that state the anti-candida properties of the aqueous extract of C. citratus; most of them studied the EO extract rather than any formulations. A previous study showed that the water and ethanolic extracts of C. citratus oils inhibited the growth of Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and C. albicans at 12.5% [44]. Multiple studies showed that the C. citratus EO extract revealed significant inhibition of biofilm formation of C. tropicalis at MIC 90 of 2.5 µL/mL [45,46], C. albicans at MIC 90 of 2.5 µL/mL [20,46], C. krusei, C. parapsilosis MIC90 of 2.5 µL/mL [46], and C. glabrata [46,47].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are few studies that state the anti-candida properties of the aqueous extract of C. citratus; most of them studied the EO extract rather than any formulations. A previous study showed that the water and ethanolic extracts of C. citratus oils inhibited the growth of Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and C. albicans at 12.5% [44]. Multiple studies showed that the C. citratus EO extract revealed significant inhibition of biofilm formation of C. tropicalis at MIC 90 of 2.5 µL/mL [45,46], C. albicans at MIC 90 of 2.5 µL/mL [20,46], C. krusei, C. parapsilosis MIC90 of 2.5 µL/mL [46], and C. glabrata [46,47].…”
Section: Discussionmentioning
confidence: 95%
“…All these studies agree with the current findings about the anti-candida effects of C. citratus. Another study showed that the residues of ethanolic and aqueous C. citratus EO extracts had a significant inhibitory effect against C. albicans due to the phytochemical composition rich in alkaloids, flavonoids, glycosides, phenols, saponins, terpenes, tannins, fatty acids, and couarins [44]. Also, C. citratus EO extracts induced a ZOI diameter of 18.00-2.46 mm in the growth of C. krusei, which was thought to be because of its strong antioxidant activity (84%) [48].…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial activity was determined by measuring the diameters of inhibition zones for each strain. The same protocol proceeded after disc saturation with the same concentration of both plant extract; the crud and the essential oil in each experiment were repeated twice (Mohammed et al 2020).…”
Section: Antibacterial Activity Of Lemongrass Crud Extract and Volati...mentioning
confidence: 99%
“…After the incubation at 37 o C for 18 to 24 h, 20 µL of the resazurin dye (0.015 per cent) was added to all the wells to determine the dye reduction (from purple to pink) and thereby the bacterial inhibition. The lowest concentrations of andrographolide and hordenine without visible growth were designated as MIC (Mohammed et al, 2020). The experiment was repeated thrice.…”
Section: Modified Resazurin Microtiter Plate Assay Proceduresmentioning
confidence: 99%